Magnetic Resonance Cholangiography with Mangafodipir Trisodium in Caroli's Disease with Pancreas Involvement - Maurea, Simone; Mollica, Carmine; Imbriaco, Massimo; Fusari, Mario; Camera, Luigi; Salvatore, Marco (JOP. Journal of the Pancreas, 2010)
Context Caroli’s disease is a rare congenital disorder first described by Caroli in 1958. This abnormality consists of non-obstructive, saccular or fusiform dilation of the intrahepatic bile ducts resulting in cystic lesions; similar abnormalities may also occur in the kidneys and pancreas. Case report We illustrate the role of enhanced mangafodipir trisodium magnetic resonance imaging in a patient with sporadic non-hereditary Caroli’s disease associated with pancreatic involvement in which mangafodipir trisodium magnetic resonance imaging characterized part of the cystic liver lesions as saccular dilations of the intrahepatic bile ducts of the left lobe, allowing diagnosis of the disease. Conclusion We strongly recommend hepatobiliary magnetic resonance imaging with mangafodipir trisodium in such patients. Image: Hydrographic imaging.